Pemanfaatan Limbah Botol Plastik sebagai Media Pembelajaran Penjernihan Air Mata Pelajaran IPAS Kelas V Mi Jami’yatul Mubtadi’in - Ainun Izza Afkarina; Muhammad Suwignyo Prayogo; Bella Rizki Prahadiyanti (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
his research examines the use of plastic bottle waste as a learning medium for water purification practices in the IPAS subject at MI Jami’yatul Mubtadi’in.The researcher also conducted direct observations at the school to see the actual implementation of this media.The results show that used plastic bottles are effective because they are easy to obtain, inexpensive, and relevant to environmental issues.This media helps students understand the concept of water purification concretely, as well as fostering environmental awareness and recycling skills.The integration of this media can enhance scientific understanding, critical thinking, and environmental awareness.Through observations at Mi Jamiyatul Mubtadiin, the children were enthusiastic in participating in the water purification practical.